The relationship between Internet addiction and childhood trauma in adolescents: The mediating role of social support - Sheng, Xuanlian; Yang, Meng; Ge, Menglin; Zhang, Ling; Huang, Cui; Cui, Shu; Yuan, Qiuyu; Ye, Mengting; Zhou, Ruochen; Cao, Panpan; Peng, Ran; Zhang, Kai; et al. (Frontiers in Psychology, 2022)
Background: Adolescents are at high risk of Internet addiction (IA). Previous studies have shown that the occurrence of Internet addiction may be associated with childhood trauma and social support to varying degrees. This study aimed to investigate the pathogenesis of Internet addiction in adolescents. Further, to explore the potential mediating role of social support in childhood trauma and Internet addiction. This study provides theoretical support for future interventions targeting Internet addiction in adolescents. Methods: This study used a descriptive cross-sectional design. The Childhood Trauma Questionnaire (CTQ), Social Support Rating Scale (SSRS), and Young's Internet Addiction Test (IAT) were used to conduct an anonymous questionnaire survey among randomly selected adolescents aged less than 18 years old in two cities in southern Anhui Province. Descriptive statistics and correlation analysis were used to test the correlation between IA and other variables. A binary logistic regression model was used to explore the influencing factors of Internet addiction. Multiple regression models were examined with process macro and bootstrapping to confirm significant mediating effects. Results: A total of 844 adolescents, equally divided between males and females, participated in this study, and the prevalence of Internet addiction in the region was 23.0%. Through the mediation test, the direct effect of childhood trauma on IA was 0.15 (95% CI [0.07,0.22], p<0.001), and the mediating effect of social support on childhood trauma and IA was 0.08 (95% CI [0.05, 0.12]). Conclusion: The study showed that childhood trauma significantly affected the incidence of IA in adolescents. Social support had a significant mediating effect on childhood trauma and IA and attenuated its negative effects.